Guessing the Form of Human Rights in a State of Law - Shivana, Nur - (Universitas Negeri Semarang, 2017)
This book on the rule of law and human rights contains material that explains how the rule of law is related to human rights. Of course, the material discussed in this book is closely related to Indonesia because we know that in the 1945 Constitution Article 1 Paragraph 3 reads that